The Knowledge Accumulation and Transfer in Open-Source Software (OSS) Development - KIM, Youngsoo (Institutional Knowledge at Singapore Management University, 2015)
We examine the learning curves of individual software developers in Open-Source Software (OSS) Development. We collected the dataset of multi-year code change histories from the repositories for 20 open source software projects involving more than 200 developers. We build and estimate regression models to assess individual developers' learning progress (in reducing the likelihood they make a bug). Our estimation results show that developer's coding and indirect bug-fixing experiences do not decrease bug ratios while bug-fixing experience can lead to the decrease of bug ratio of learning progress. We also find that developer's coding and bug-fixing experiences in other projects do not decrease the developer's bug ratio in a focal project. We empirically confirm the moderating effects of bug types on learning progress. Developers exhibit learning effects for some simple bug types (e.g., Wrong literals) or bug types with many instances (e.g., Wrong if conditionals). The results may have managerial implications and provoke future research on project management about allocating resources on tasks that add new code versus tasks that debug and fix existing code.